(untitled) (Faridpur Medical College Journal, 2013)
Rupture uterus is a rare and often catastrophic condition. It is associated with a high incidence of fetal and maternal mortality and morbidity. Our objective in this study is to determine incidence, etiology, trend, management, maternal and fetal outcome of uterine rupture in Faridpur Medical College Hospital. This is a prospective cross-sectional study of patients with ruptured uterus from the period of January 2011 to December 2011 admitted at Faridpur Medical College Hospital. All the cases of ruptured uterus who were either admitted with uterine rupture or who developed it in hospital were included in the study. Patients having ruptured uterus due to congenital anomaly were excluded from the study. Patients were initially assessed in labour ward, relevant sociodemographic data, previous antenatal and surgical history recorded. Ways of management, maternal and fetal outcome were taken for analysis. There were 30 cases of ruptured uterus out of total 3606 deliveries (including 1809 caesarian sections) over a one year time period, with a prevalence of 0.83%. The most common age group was 21-30 years. A majority of patients 16(53.3%) were cases of unscarred uterus presenting with rupture; the common cause of rupture in scarred uterus was injudicious use of oxytocin (13,43.33%). Proper antenatal care, appropriate counseling of patients with history of previous caesarian section for hospital delivery, training of skilled birth attendant can reduce mortality and morbidity due to rupture uterus. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13504 Faridpur Med. Coll. J. 2012;7(2):79-81